2009
DOI: 10.4315/0362-028x-72.8.1769
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination of the Cyanobacterial Toxin β-N-Methylamino-L-Alanine in Algae Food Supplements, Freshwater Fish, and Bottled Water

Abstract: Beta-N-Methylamino-L-alanine (BMAA) is a neurotoxin originally found in cycad seeds and now known to be produced by many species of freshwater and marine cyanobacteria. We developed a method for its determination in blue-green algae (BGA) food supplements, freshwater fish, and bottled water by using a strong cation-exchange, solid-phase extraction column for cleanup after 0.3 M trichloroacetic acid extraction of BGA supplements and fish. Bottled water was applied directly onto the solid-phase extraction column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…The reported L-BMAA concentrations in the aquatic environment vary widely between studies ranging from ng/g dry weight to low mg/g dry weight range in phytoplankton (Jonasson et al, 2010;Faassen, 2014). Concentrations similar to those for phytoplankton were reported also in animals used for human consumption, such as crabs, oysters, mussels, fish and algae food supplements (Scott et al, 2009;Jonasson et al, 2010;Niedzwiadek et al, 2012;Jiang et al, 2014b;Reveillon et al, 2015;Salomonsson et al, 2015). Considering that L-BMAA biosynthesized by symbiotic or/and freeliving cyanobacteria can accumulate in organisms and can biomagnify in the food web, both in free amino acid and proteinbound forms, concentrations in organisms can increase significantly.…”
Section: Discussionmentioning
confidence: 85%
“…The reported L-BMAA concentrations in the aquatic environment vary widely between studies ranging from ng/g dry weight to low mg/g dry weight range in phytoplankton (Jonasson et al, 2010;Faassen, 2014). Concentrations similar to those for phytoplankton were reported also in animals used for human consumption, such as crabs, oysters, mussels, fish and algae food supplements (Scott et al, 2009;Jonasson et al, 2010;Niedzwiadek et al, 2012;Jiang et al, 2014b;Reveillon et al, 2015;Salomonsson et al, 2015). Considering that L-BMAA biosynthesized by symbiotic or/and freeliving cyanobacteria can accumulate in organisms and can biomagnify in the food web, both in free amino acid and proteinbound forms, concentrations in organisms can increase significantly.…”
Section: Discussionmentioning
confidence: 85%
“…For sixteen methods, most data needed for method validation (detection limits, linear range, precision and recovery) were provided [34,76,79,82,93,94,100,105,111,121,122,135,145,148]. However, unvalidated methods (or methods for which no sufficient validation data were provided) were repeatedly referred to as 'validated'.…”
Section: Methods Performancementioning
confidence: 99%
“…The two studies in which no BMAA was detected in higher aquatic organisms (fish and shrimp) have used LC-FLD analysis (LOD 0.21 µg/g DW for fish and 0.3 µg/g DW for shrimp [147,148]). Although it is shown that BMAA can be present in aquatic ecosystems, this conclusion is only based on a narrow selection of articles ( Figure 5.4).…”
Section: Presence Of Bmaa In Aquatic Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations